QUANTITATIVE ASSESSMENT OF CYBER PROTECTION OF INFORMATION - Khoroshko, Volodymyr; Khokhlachova, Yuliia; Vishnevska, Natalia; Chobal, Oleksandr; Venherskyi, Petro (Ukrainian Information Security Research Journal, 2023)
The creation, implementation and operation of computer systems has led to new problems in the field of information security. Cyber defense of information technology should be appropriate in its characteristics to the scale of threats and risks. Deviation from this rule will lead to significant losses. Each computer system (CS) must have its own optimal level of cyber security, which must be constantly maintained. Unfortunately, there is still no adequate methodology for assessing the quantitative level of cyber security. The main problems that need to be solved to develop the mathematical foundations of quantitative analysis of cyber security and determine its level are: determining the functional relationship between the methods of attack on the CS and the methods of short circuit; development of a criterion for assessing the level of short-circuit, based on the totality of its quantitative characteristics; determining the methodology for substantiating priority measures aimed at ensuring a given level of cyber security of information. The proposed technique will enable the use of new methods of information processing in order to assess its cyber security, which were not previously used.